Impact of Fungi Co-occurrence on Mycotoxin Contamination in Maize During the Growing Season - Giorni, Paola; Bertuzzi, Terenzio; Battilani, Paola (Frontiers in Microbiology, 2019)
Maize is a possible host of many fungi, some of them able to produce different mycotoxins. Few studies exist on co-occurring fungi and resulting multi-mycotoxin contamination in field; for this reason, in field trials were conducted in two consecutive years to verify fungal incidence and mycotoxin production in the case of the co-occurrence of the 3 main mycotoxigenic fungi of maize in Italy: Aspergillus flavus, Fusarium verticillioides and F. graminearum able to produce, respectively, aflatoxin B1 (AFB1), fumonisins (FBs) and deoxynivalenol (DON). Artificial inoculation was done after silk emergence of maize and samples were collected with a 2 week schedule up to harvest time (4 samplings). Fungal interaction resulted as playing a role for both fungal incidence and mycotoxins production, as did weather conditions too. Main interactions were noted between A. flavus and F. verticillioides, and between F. verticillioides and F. graminearum. In particular, as a result of fungal co-occurrence, AFB1 resulted stimulated by F. graminearum presence while no effects were noted in FBs and DON in case of F. verticillioides-F. graminearum co-occurrence. Interestingly, the co-presence of A. flavus significantly reduced both FB and DON production.